Identification and functional characterization of interferon c (IFNc) in orange-spotted grouper (Epinephelus coioides) involved in antiviral response to SGIV and RGNNV infections - Yanjie Shi; Rui Jiang; Xiaotian Zhuo; Jiaji Chen; Zhiwen Wang; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Defect-engineered Bi2O2S/Co3O4 heterostructure on sunflower pith for synergistic solar-driven interfacial evaporation and VOC degradation - Tingting Jiang; Siyu Huang; Zhuo Li; Rui Zhao; Haifeng Zhang (Chemical Engineering Journal, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

In situ synthesized Ag nanoparticles encapsulated inside carbonized ZIF-8 for efficient Cr(VI) reduction - Haojie Zhang; Zhuo-Rui Jiang; Yu-Xiao Zhou; Rui Chen; Hongmei Jiang; Ying Li (Journal of Environmental Chemical Engineering, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Structure of a novel Co-based heterogeneous catalyst via Mn3(PO4)2 as a carrier to efficiently activate peroxymonosulfate for improving degradation of sulfonamides - Yuxin Li; Zhuo-Rui Jiang; Xiaoli Yang; Yeqing Lan; Jing Guo (Chemosphere, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Efficient removal of nitrogen from tidal flow constructed wetlands based on the in-situ zeolite regeneration: Measures and mechanisms - Rui Ma; Jiangsen Ma; Yuzhe Chen; Yiyuan Zhuo; Linsong Cheng; Lei Jiang; Yuanxiang Mao; Qiushi Shen; Caocun Liu; Fangying Ji (Chemical Engineering Journal, 2023)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Alkaloids from Juglans Mandshurica maxim induce distinctive cell death in hepatocellular carcinoma cells - Li-Li Lou; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2019)

Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Xiao-jun Wang; Jian-yun Zhang; Mahtab Ali; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Zhuo Jiang (Mitigation and Adaptation Strategies for Global Change, 2016)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)